Water Quality Measurement and Filtering Tools Using Arduino Uno, PH Sensor and TDS Meter Sensor - Yuda Irawan; Anita Febriani; Refni Wahyuni; Yesica Devis (Journal of Robotics and Control (JRC), 2021)
Rusunawa Rejosari is a flats owned by the Pekanbaru city government which is inhabited by underprivileged residents, water in the Rusunawa Rejosari borehole emits an unpleasant and murky odor, making it unfit for consumption and use for daily needs by residents who live there. Indonesia issued the TDS Standard by the Ministry of Health and the Indonesian National Standard (SNI), which is a maximum value of 500 ppm TDS and for the standard Hydrogen Potential (PH) of clean water 6.6 - 9.0 PH. Based on the above problems, a Water Quality Measurement and Filtration Tool was made using Arduino, a Hydrogen Potential Sensor (PH) and a Total Dissolved Solids (TDS) Sensor. Based on the research that has been carried out, it can be concluded that the tool runs smoothly, as evidenced by the measurement results of the accuracy of the sensor and successfully filters the water when the measurement is not normal, so that the water is suitable for consumption and use.